Spatial and temporal evolution of ecotourism development level and its driving factors under the perspective of sustainable development: the case of Ili river valley - Pengkai Zhao; Haojie Sun; Jiangling Hu; Xinyu Zhao; Changying Song; Xueting Xu (PLoS ONE, 2025)
Ecotourism, as an ideal model for sustainable tourism development, is a response to ecological problems and the way tourism is developed. The foundational elements of ecotourism serve as the basis for the development level evaluation index system. Ten counties and cities in the Ili River Valley are evaluated for their level of ecotourism development between 2010 and 2019 using the entropy weight TOPSIS approach. Using the standard deviation ellipse, classic Markov chain, and spatial Markov chain, the temporal and spatial evolution characteristics are examined. Geographic detectors are utilized to explore the driving factors of ecotourism development. The data indicates that: (1) With a notably diverse spatial structure, the growth rate of ecotourism varies among the counties and cities in the Ili River Valley. (2) The level of comprehensive ecotourism development is continuously improving, with significant gradient differences in spatial distribution, forming a dynamic spatial pattern of ‘high in the north and low in the south.’ (3) The standard deviation ellipses of each year show a “northwest – southeast” direction, and basically form a stable migration rule from northwest to southeast; (4) The level of tourism income and economic development have a significant impact on the development of ecotourism, and the influence of tourism reception capacity and industrial structure level is gradually enhanced, while the promotion effect of ecological environment level is not significant. The interaction of the two factors is greater than that of the single factor, indicating that the interaction connection is facilitated by the two elements. The findings of the study can offer some theoretical underpinnings and scientific references for raising the degree of ecotourism development and encouraging the Ili River Valley's tourism industry's sustainable growth.